2000
DOI: 10.1029/2000ja900109
|View full text |Cite
|
Sign up to set email alerts
|

Magnetopause motion driven by interplanetary magnetic field variations

Abstract: Abstract. We use previously reported observations of hot flow anomalies (HFAs) and foreshock cavities to predict the characteristics of corresponding features in the dayside magnetosheath, at the magnetopause, and in the outer dayside magnetosphere. We compare these predictions with Interball 1, Magion 4, and GOES 8/GOES 9 observations of magnetopause motion on the dusk flank of the magnetosphere from 1800 UT on January 17 to 0200 UT on January 18, 1996. As the model predicts, strong (factor of 2 or more) dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 28 publications
(20 reference statements)
4
63
0
Order By: Relevance
“…Fairfield et al (1990), using AMPTE and GOES data, found that correlated density and field perturbations, due to local solar wind bow shock interaction, were responsible for compressions of the magnetosphere. Sibeck et al (2000) presented a case study in which it was possible to identify a causal chain for transient magnetopause motion observed at geosynchronous orbit, tracking pressure variations through the magnetosheath, to their origin: changes in the solar wind magnetic field interacting with the bow shock excavating cavities. Murr and Hughes (2003) were able to identify foreshock cavities as the triggers of several travelling convection vortices in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Fairfield et al (1990), using AMPTE and GOES data, found that correlated density and field perturbations, due to local solar wind bow shock interaction, were responsible for compressions of the magnetosphere. Sibeck et al (2000) presented a case study in which it was possible to identify a causal chain for transient magnetopause motion observed at geosynchronous orbit, tracking pressure variations through the magnetosheath, to their origin: changes in the solar wind magnetic field interacting with the bow shock excavating cavities. Murr and Hughes (2003) were able to identify foreshock cavities as the triggers of several travelling convection vortices in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Furthermore, an influence of other parameters on locations of both boundaries was examined in different papers; for example, a rotation of the direction of the magnetic field across the magnetosheath [Pudovkin et al, 1982], both IMF polar and azimuthal angles, and the angle between the IMF and the bow shock normal [Laakso et al, 1998;Šafránková et al, 2003], IMF B Y component [Sibeck et al, 2000], or Alfvénic fluctuations dominating the solar wind [Tsubouchi et al, 2000]. Moreover, larger displacements of boundaries as a result of their interaction with different solar wind discontinuities (e.g., HFAs, strong interplanetary shocks, pressure pulses) were widely discussed by many authors [e.g., Sibeck et al, 1999;Farrugia et al, 2008;Zhang et al, 2009;Jacobsen et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Foreshock signature which can lead to striking P d variations, such as the foreshock cavity, is generally characterized by a region of depressed P d bounded by enhancements on one or both sides. Its effect on the dayside geosynchronous magnetic field is the decrease of field strength bounded by enhancements according to Sibeck et al (2000). Therefore, if foreshock played a significant role in the present study, there would exist a time interval during which the observed magnetic field was apparently smaller than the simulated one, while larger than it on the leading or/and trailing sides.…”
Section: Possible Influences Of the Foreshock Regionmentioning
confidence: 85%